Heavy Alkali Metal Manganate Complexes: Synthesis, Structures and Solvent‐Induced Dissociation Effects. Issue 55 (3rd August 2022) - Ballmann, Gerd M.; Gentner, Thomas X.; Kennedy, Alan R.; Hevia, Eva; Mulvey, Robert E.
Abstract: Rare examples of heavier alkali metal manganates [(AM)Mn(CH2 SiMe3 )(N 'Ar )2 ∞ ] (AM=K, Rb, or Cs) [N 'Ar =N(SiMe3 )(Dipp), where Dipp=2, 6‐ i Pr2 ‐C6 H3 ] have been synthesised with the Rb and Cs examples crystallographically characterised. These heaviest manganates crystallise as polymeric zig‐zag chains propagated by AM⋅⋅⋅π‐arene interactions. Key to their preparation is to avoid Lewis base donor solvents. In contrast, using multidentate nitrogen donors encourages ligand scrambling leading to redistribution of these bimetallic manganate compounds into their corresponding homometallic species as witnessed for the complete Li ‐ Cs series. Adding to the few known crystallographically characterised unsolvated and solvated rubidium and caesium s‐block metal amides, six new derivatives ([AM(N 'Ar )∞ ], [AM(N 'Ar )⋅TMEDA∞ ], and [AM(N 'Ar )⋅PMDETA∞ ] where AM=Rb or Cs) have been structurally authenticated. Utilising monodentate diethyl ether as a donor, it was also possible to isolate and crystallographically characterise sodium manganate [(Et2 O)2 Na( n Bu)Mn[(N 'Ar )2 ], a monomeric, dinuclear structure prevented from aggregating by two blocking ether ligands bound to sodium. Abstract : Heavy alkali metal alkyls can form ate compounds with manganese bis(amides) when donor solvents are absent but introducing the common donors TMEDA or PMDETA leads to breakdown of the ates together with ligand exchange, which results in the formation of new solvated heavier alkali metal amides and alkylmanganese amides.